Treatment of patient with open fracture of ulnar bone - A. L. Kameka (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The article presents the result of treatment of patient P. with trauma caused by an attack of a bear during the hunting. Patient had open comminuted displaced fracture of the lower third of right ulnar bone with formation of large infected wound of right forearm and right hand with injury of flexor tendons of IV and V fingers, extensor tendon of V finger, ulnar nerve. At the admission to the Central District Hospital of Mama, primary surgical treatment of wound, plaster immobilization were conducted, wound weren't stitched up. At the treatment in Irkutsk Scientific Center of Surgery and Traumatology, secondary surgical treatment of wound of right forearm, necretomy, ultrasound treatment of wound, laceration repair of wound with local tissues, transosseous osteosynthesis of right forearm - hand were conducted. As a result of conducted treatment we achieved total reduction of necrotic and purulent process, repair of vast infected wound of forearm and hand, full adhesion of fracture of ulnar bone and restoration of a function of right arm. Using ultrasound treatment of wounds and transosseous osteosynthesis at openfractures of forearm bones and chronic purulent infection is a treatment of choice and can cause good clinical outcome.